Contribuições para o ensino da geometria nos anos iniciais do ensino fundamental em uma cidade de Minas Gerais - Moraes, Elton Rodrigo de (2021)
Studies show that in the early years of elementary school, Mathematics, and especially Geometry, are often neglected. This is due to a number of factors, such as the fact that most teachers in the early years of elementary school (1st to 5th year) have training in Teaching and Pedagogy courses, which have little Mathematics content in their grid curriculum (CAZORLA; SANTANA, 2005), (CLESAR; GIRAFFA, 2020). Sousa (2019) studied the pedagogy courses in Minas Gerais and pointed to this reality. For Lorenzato (1995), this is one of the main reasons that contribute to the lack of geometric knowledge needed by teachers and, consequently, result in a deficient teaching of Geometry. Thinking of changing this scenario, the Municipality of Pouso Alegre - MG, in 2019, included one class of Geometry per week in the early years of elementary school, being taught by a specific teacher with a degree in Mathematics. The objective of this work, is to contribute to the teaching of Geometry in the early years, reporting the pedagogical practices adopted by the teachers of Geometry in the classroom, in addition to the difficulties encountered. A qualitative field research was carried out with a semi-structured interview. The collected data was analyzed using the method of content analysis proposed by Bardin (1977).